Lithium metal negative electrode artificial protective layer and preparation method and application thereof
Patent Information
- Application Number
- CN202610928750.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-06-25
- Publication Date
- 2026-10-09
AI Technical Summary
[0002]锂金属电池因其具备极高的理论比容量(3860mAhg-1)和极低的氧化还原电势(-3.04Vvs标准氢电极),被公认为下一代高能量密度储能器件的核心候选体系,在电动汽车、便携式电子设备及大规模储能领域展现出巨大的应用潜力;然而,锂金属负极在充放电过程中存在两大核心瓶颈问题:一是充放电时锂金属不均匀沉积形成锂枝晶,枝晶刺穿隔膜易引发电池短路、热失控等安全隐患;二是锂金属与电解液自发形成的固体电解质界面(SEI)膜结构疏松、成分不均、机械强度低,导致界面副反应持续发生,电解液不断消耗,电池容量快速衰减,严重制约了锂金属电池的商业化进程
本发明提出一种锂金属负极人工保护层及其制备方法与应用,通过将包含咪唑阳离子的离子液体聚合物溶于有机溶剂得到涂覆液,并将其施加于锂金属基底表面形成人工保护层,利用聚乙烯主链以及含咪唑阳离子侧链所提供的优异机械柔韧性和界面相容性,有效缓冲锂金属在充放电循环中的体积变化,维持保护层在长期循环过程中的结构完整性;同时,侧链的氟化磺酰亚胺阴离子在锂金属界面处富集,能够有效诱导形成富含LiF、LiN、Li2O等无机相的稳定SEI层,该SEI层兼具高机械强度与优异的锂离子传输性能,可显著降低界面阻抗、提供均匀的锂离子通量和成核位点,从根源上抑制锂枝晶的形核与生长,避免电池短路风险;此外,本发明采用溶液涂覆法成膜,工艺简便、条件温和、无需昂贵试剂和复杂设备,成膜均匀且膜层厚度可通过溶液浓度和涂覆次数精准调控,易于实现规模化生产。
Smart Images

Figure CN122889704A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of lithium metal battery technology, specifically to an artificial protective layer for lithium metal anodes, its preparation method, and its application. Background Technology
[0002] Lithium metal batteries are known for their extremely high theoretical specific capacity (3860 mAh g). -1 With its extremely low redox potential (-3.04V vs standard hydrogen electrode), lithium metal anode is widely recognized as a core candidate system for next-generation high-energy-density energy storage devices, showing great application potential in electric vehicles, portable electronic devices, and large-scale energy storage. However, lithium metal anodes face two major bottlenecks during charge and discharge: First, uneven deposition of lithium metal during charge and discharge forms lithium dendrites, which can easily cause battery short circuits, thermal runaway, and other safety hazards by piercing the separator. Second, the solid electrolyte interphase (SEI) film spontaneously formed between lithium metal and electrolyte has a loose structure, uneven composition, and low mechanical strength, leading to continuous interfacial side reactions, continuous electrolyte consumption, and rapid capacity decay, which seriously restricts the commercialization of lithium metal batteries.
[0003] Artificial protective layer technology, by pre-constructing a stable functional film layer on the lithium metal surface, can precisely control lithium deposition behavior, inhibit dendrite growth, and optimize SEI structure, becoming one of the key technologies to solve the bottleneck problem of lithium metal anodes. Among many protective layer materials, polymers have become an ideal choice for artificial protective layers on lithium metal surfaces due to their chemical and electrochemical stability and good flexibility.
[0004] Although polymer-based artificial protective layer technology provides an effective way to improve the performance of lithium metal anodes, the current technology still has the following core shortcomings: Low ion transport efficiency: Most polymer-based protective layers have a simple design, making it difficult to achieve anion enrichment at the interface and effectively induce the formation of an inorganic-rich SEI layer. This results in poor ion transport performance and high interface impedance of the SEI layer, which restricts the rate performance of the battery.
[0005] The preparation process is complex: existing film preparation methods rely on spin coating, drop coating, and blade coating, which make it difficult to achieve large-area uniform film formation and are not conducive to large-scale production.
[0006] Insufficient stability: Some artificial protective layers are prone to swelling or degradation in the electrolyte, making them unable to adapt to the harsh environment of long-term cycling of lithium metal batteries and limiting the battery's lifespan. Summary of the Invention
[0007] The purpose of this invention is to overcome the shortcomings of the prior art and provide an artificial protective layer for lithium metal anodes, its preparation method, and its application.
[0008] To achieve the above objectives, the present invention provides the following technical solution: This application provides a method for preparing an artificial protective layer for lithium metal anodes, comprising the following steps: Step S1: Dissolve the ionic liquid polymer containing imidazole cations in an organic solvent to obtain a coating solution; Step S2: Apply the coating liquid to the surface of the lithium metal substrate and remove the organic solvent to form the artificial protective layer on the surface of the lithium metal substrate.
[0009] Preferably, the ionic liquid polymer is a hydrophobic ionic liquid polymer prepared by an ion exchange reaction; the ion exchange reaction occurs between the imidazolium halide polymer and the bis(fluorosulfonyl)imide salt.
[0010] Preferably, prior to step S1, the preparation method further includes the step of preparing the ionic liquid polymer: providing an aqueous solution of an imidazolium halide polymer; introducing a bis(fluorosulfonyl)imide salt into the aqueous solution to generate a precipitate containing the hydrophobic ionic liquid polymer; separating and washing the precipitate until no halogen ions are detectable in the washing solution.
[0011] Preferably, the ionic liquid polymer is poly(1-butyl-3-vinylimidazolium bis(fluorosulfonyl)imide); the organic solvent is dimethyl sulfoxide; and the application method is brushing.
[0012] Preferably, the mass concentration of the coating solution is 0.1 to 10.0 g / mL, and the organic solvent is removed by heat treatment at 40 to 80°C in step S2.
[0013] An artificial protective layer for a lithium metal anode comprises a poly(1-alkyl-3-vinylimidazolium) ionic liquid polymer, wherein the ionic liquid polymer comprises a polyethylene backbone and an imidazole cationic side chain, wherein the imidazole cation forms an ionic bond with a fluorinated sulfonamide anion.
[0014] Preferably, the fluorinated sulfonyl imide anion is a bis(fluorosulfonyl)imide anion, and the alkyl group is butyl; the artificial protective layer is prepared by the above method.
[0015] A modified lithium metal anode, comprising: Lithium metal substrate; and A protective layer covering at least one side surface of the lithium metal substrate, wherein the protective layer is the aforementioned artificial protective layer.
[0016] A lithium metal battery includes a positive electrode, an electrolyte, a separator, and a modified lithium metal negative electrode as described above.
[0017] A method for preparing an ionic liquid polymer, comprising: In the presence of a free radical initiator, 1-vinyl-3-alkylimidazolium halide monomers are polymerized in an organic solvent to obtain poly(1-alkyl-3-vinylimidazolium) halide; The poly(1-alkyl-3-vinylimidazolium) halide salt and the bis(fluorosulfonyl)imide salt are subjected to an ion exchange reaction in an aqueous solution to generate an ionic liquid polymer precipitate containing poly(1-alkyl-3-vinylimidazolium bis(fluorosulfonyl)imide). The precipitate was separated and purified from the reaction mixture to obtain the ionic liquid polymer.
[0018] Compared with the prior art, this application has the following beneficial effects: This invention proposes an artificial protective layer for lithium metal anodes, its preparation method, and its application. A coating solution is obtained by dissolving an ionic liquid polymer containing imidazole cations in an organic solvent and applying it to the surface of a lithium metal substrate to form an artificial protective layer. Utilizing the excellent mechanical flexibility and interfacial compatibility provided by the polyethylene backbone and imidazole-containing cation-containing side chains, the layer effectively buffers the volume changes of lithium metal during charge-discharge cycles, maintaining the structural integrity of the protective layer during long-term cycling. Simultaneously, the fluorinated sulfonyl imide anions of the side chains accumulate at the lithium metal interface, effectively inducing the formation of a stable SEI layer rich in inorganic phases such as LiF, LiN, and Li2O. This SEI layer possesses both high mechanical strength and excellent lithium-ion transport performance, significantly reducing interfacial impedance, providing uniform lithium-ion flux and nucleation sites, and fundamentally inhibiting the nucleation and growth of lithium dendrites, thus avoiding the risk of battery short circuits. Furthermore, this invention employs a solution coating method for film formation, which is simple, mild, requires no expensive reagents or complex equipment, produces uniform films, and allows for precise control of film thickness through solution concentration and coating cycles, facilitating large-scale production. Attached Figure Description
[0019] Figure 1 The diagram shows the cycle performance of a symmetric battery prepared based on an embodiment of the present invention.
[0020] Figure 2 The graph shows the cycle performance of the LCO / PVIMFSI@Li battery prepared based on the embodiments of the present invention and the comparative sample LCO / Li battery.
[0021] Figure 3 This is a flowchart illustrating the preparation method of an artificial protective layer for lithium metal anodes. Detailed Implementation
[0022] The technical solutions of the present invention will be clearly and completely described below with reference to the accompanying drawings of the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. All other embodiments obtained by those skilled in the art based on the embodiments of the present invention without creative effort are within the scope of protection of the present invention.
[0023] Furthermore, in this invention, an element referred to as fixed to or disposed on another element may be directly disposed on the other element, or there may be an intermediate element; when an element is considered to be connected to another element, it may be directly connected to the other element, or there may be an intermediate element at the same time; the terms vertical, horizontal, left, right and similar expressions used herein are for illustrative purposes only and do not represent the only implementation.
[0024] It should be noted that: The core design concept of the artificial protective layer for lithium metal anodes provided by this invention lies in: using polyimide-based ionic liquid polymers as the main material of the artificial protective layer; utilizing the polyethylene backbone and imide-containing cationic side chains to impart excellent mechanical flexibility and interfacial compatibility to the protective layer; and simultaneously introducing fluorinated sulfonyl imide anions (such as bis(fluorosulfonyl)imide anions, FSI) through the side chains. - This process enriches the anions at the lithium metal anode interface, inducing the formation of a high-mechanical-strength SEI layer rich in inorganic components such as LiF, LiN, and Li2O. This inorganic-rich SEI layer exhibits excellent lithium-ion transport performance, effectively reducing interfacial impedance, providing uniform lithium-ion flux and nucleation sites, and fundamentally inhibiting the nucleation and growth of lithium dendrites. Simultaneously, the good flexibility and film-forming properties of the polymer backbone can effectively buffer volume changes during lithium deposition / stripping, maintaining the long-term integrity of the film structure.
[0025] The inventive technical points of this invention are mainly reflected in the following aspects: This invention is the first to apply a specific ionic liquid polymer, poly(1-alkyl-3-vinylimidazolium bis(fluorosulfonyl)imide), to an artificial protective layer for lithium metal anodes. Compared to traditional polymer protective layer materials, this ionic liquid polymer combines the high ionic conductivity of ionic liquids with the good film-forming properties and mechanical flexibility of polymers. Crucially, FSI... - Anions can preferentially adsorb and accumulate at the lithium metal interface, and participate in the formation of SEI in situ during electrochemical cycling, inducing the generation of an SEI layer rich in inorganic components such as LiF. This is a key scientific innovation for achieving excellent interface performance.
[0026] This invention employs a two-step method combining free radical polymerization and ion exchange to prepare the target ionic liquid polymer. In the polymerization stage, a well-defined poly(1-vinyl-3-butylimidazolium) bromide containing imidazole cationic side chains is obtained through controlled free radical polymerization. In the ion exchange stage, utilizing the property of the hydrophobic ionic liquid polymer to precipitate in aqueous solution, bromide ions can be converted to FSI through simple precipitation and washing operations. - The efficient replacement of anions avoids complex column chromatography or dialysis purification steps; in addition, the brush coating method for film formation is easier to achieve large-area uniform coating and precise control of film thickness compared with traditional laboratory methods such as spin coating and drop coating, and the process has good prospects for scale-up.
[0027] Traditional polymer protective layers are mostly passive physical barriers, relying solely on mechanical blocking to delay dendrite growth. The PVI MFSI protective layer of this invention, however, possesses active interface regulation capabilities, and its FSI... - Anions can participate in interfacial electrochemical reactions, inducing the formation of an inorganic-rich SEI layer with high mechanical strength and excellent ion transport performance. This innovation in mechanism, which transforms passive protection into active regulation, is the fundamental reason for the significant improvement in battery performance.
[0028] See Figure 3 This application provides a method for preparing an artificial protective layer for lithium metal anodes, comprising the following steps: Step S1: Dissolve the ionic liquid polymer containing imidazole cations in an organic solvent to obtain a coating solution.
[0029] Step S2: Apply the coating liquid to the surface of the lithium metal substrate and remove the organic solvent to form the artificial protective layer on the surface of the lithium metal substrate.
[0030] In this embodiment, the ionic liquid polymer containing imidazole cations is specifically poly(1-butyl-3-vinylimidazolium bis(fluorosulfonyl)imide) (PVIMFSI); this polymer has polyethylene as the main chain, with 1-butyl-3-vinylimidazolium cations and bis(fluorosulfonyl)imide anions (FSI) on the side chains. -In step S1, the organic solvent is specifically selected as dimethyl sulfoxide (DMSO). In an argon-atmospheric glove box, PVIMFSI powder is dissolved in DMSO to prepare a uniform solution with a mass concentration of 0.1–10.0 g / mL, which serves as the coating solution. In step S2, the coating is applied by brushing: a fresh lithium metal sheet with a thickness of 0.05–0.4 mm is prepared as a substrate, and the PVIMFSI / DMSO solution is uniformly brushed onto the surface of the lithium metal sheet using a soft brush. The coated lithium metal sheet is then transferred to a heating stage at 40–60°C and heated at a constant temperature for 2–6 hours to allow the DMSO solvent to completely evaporate, forming a dense and uniform PVIMFSI artificial protective layer on the lithium metal surface, thus obtaining the modified lithium metal anode PVIMFSI@Li. The thickness of the protective layer can be controlled by adjusting the concentration of the coating solution or the number of coating cycles.
[0031] The core mechanism of this PVIMFSI artificial protective layer is as follows: the polyethylene main chain and imidazole cationic side chains provide good mechanical flexibility and interfacial compatibility, effectively buffering the volume changes caused by lithium metal deposition / stripping during charge-discharge cycles and maintaining the long-term integrity of the film structure; the FSI of the side chains... - Anions accumulate at the lithium metal interface, which can induce the formation of a stable SEI layer rich in inorganic phases such as LiF, LiN, and Li2O. This SEI layer has both high mechanical strength and excellent lithium-ion transport performance, which can significantly reduce interface impedance, provide uniform lithium-ion flux and nucleation sites, suppress the nucleation and growth of lithium dendrites from the source, and ensure the long-term cycle stability of the battery.
[0032] In one specific embodiment, the ionic liquid polymer is a hydrophobic ionic liquid polymer prepared by an ion exchange reaction; the ion exchange reaction occurs between an imidazolium halide polymer and a bis(fluorosulfonyl)imide salt.
[0033] In this embodiment, the imidazolium halide polymer is specifically poly(1-vinyl-3-butylimidazolium bromide) (PVIMBr), and the bis(fluorosulfonyl)imide salt is specifically lithium bis(fluorosulfonyl)imide (LiFSI); the PVIMBr side chain contains bromide ions (Br). - As a counter anion, it has good water solubility; while FSI in LiFSI - Anions have strong hydrophobicity; when FSI - Br is replaced by ion exchange reaction - Subsequently, the formed PVIMFSI is due to FSI - Due to its hydrophobic properties, it precipitates from aqueous solution as a precipitate, thus realizing the preparation of hydrophobic ionic liquid polymers. The PVIMMFSI prepared by this method has good solubility in organic solvents and is suitable for subsequent coating film formation processes.
[0034] In one specific embodiment, prior to step S1, the preparation method further includes the step of preparing the ionic liquid polymer: providing an aqueous solution of an imidazolium halide polymer; introducing a bis(fluorosulfonyl)imide salt into the aqueous solution to generate a precipitate containing the hydrophobic ionic liquid polymer; separating and washing the precipitate until no halogen ions are detectable in the washing solution.
[0035] In this embodiment, the specific steps for preparing the ionic liquid polymer are as follows: Weigh 1-3g of PVIMBr, add it to 20-30mL of deionized water, and stir magnetically until completely dissolved to obtain a PVIMBr aqueous solution; separately weigh 1-3g of LiFSI, add it to 20-30mL of deionized water, and stir magnetically until completely dissolved to obtain a LiFSI aqueous solution; under room temperature conditions, continuously stir the PVIMBr aqueous solution at a rate of 300-600r / min, while slowly adding the LiFSI aqueous solution dropwise over a period of 5-10min; after the addition is complete, continue stirring for 5-30min to allow the ion exchange reaction to proceed fully, and the LiFSI... - Br in anion-substituted polymer side chains - The anion reacts to form hydrophobic PVIMFSI, which precipitates from the aqueous phase as a white precipitate. The reaction mixture is centrifuged at 5000–10000 r / min for 5–10 min, the supernatant is discarded, and the white precipitate is collected. The precipitate is washed repeatedly with deionized water 2–5 times, centrifuged each time, until the washing solution shows no turbidity upon addition of silver nitrate solution, indicating that the bromide ions have been completely removed. The washed precipitate is dried in a vacuum drying oven at 60–80℃ for 12–24 h to obtain a white powdery product, PVIMFSI.
[0036] This ion exchange method utilizes the spontaneous precipitation property of hydrophobic ionic liquid polymers in the aqueous phase, leaving unreacted raw materials and water-soluble byproducts in the supernatant. They can be efficiently separated and purified by simple centrifugation and washing. The operation is simple and the process is green and environmentally friendly.
[0037] In one specific embodiment, the ionic liquid polymer is poly(1-butyl-3-vinylimidazolium bis(fluorosulfonyl)imide); the organic solvent is dimethyl sulfoxide; and the application method is brushing.
[0038] In this embodiment, the ionic liquid polymer is specifically PVIMFSI, which has the following structural features: a polyethylene main chain with 1-butyl-3-vinylimidazolium cations and FSI on the side chains. -Anions are used; the organic solvent is DMSO, which has good solubility for PVI MFSI and a moderate boiling point, making it easy to remove by subsequent heating; the application method is to use a soft brush, which is simple to operate and can achieve large-area uniform film formation. The film thickness can be precisely controlled by the solution concentration and the number of coatings.
[0039] In one specific embodiment, the mass concentration of the coating solution is 0.1 to 10.0 g / mL, and the organic solvent is removed by heat treatment at 40 to 80°C in step S2.
[0040] In this embodiment, PVIMFSI powder is dissolved in DMSO to prepare a homogeneous solution with a mass concentration of 0.1–10.0 g / mL. The coated lithium metal sheet is then transferred to a heating stage at 40–60°C and heated at this temperature for 2–6 hours to allow the DMSO to completely evaporate, forming a dense and uniform PVIMFSI artificial protective layer on the lithium metal surface. The preferred heating temperature is 40–60°C, which ensures sufficient solvent evaporation while avoiding adverse effects on the lithium metal substrate from excessively high temperatures.
[0041] An artificial protective layer for a lithium metal anode comprises a poly(1-alkyl-3-vinylimidazolium) ionic liquid polymer, wherein the ionic liquid polymer comprises a polyethylene backbone and an imidazole cationic side chain, and the imidazole cation forms an ionic bond with a fluorinated sulfonamide anion.
[0042] In one specific embodiment, the fluorinated sulfonamide anion is a bis(fluorosulfonamide)imide anion, and the alkyl group is a butyl group; the artificial protective layer is prepared by the method described above.
[0043] In this embodiment, the artificial protective layer is made of PVIMMFSI. The polymer backbone is polyethylene, with 1-butyl-3-vinylimidazolium cations in the side chains, and FSI... - The anion binds to the imidazole cation through ionic bonds; this artificial protective layer is prepared by the above method, namely, dissolving PVI MFSI powder in DMSO in an argon glove box to obtain a coating solution, uniformly coating it onto the surface of a lithium metal sheet using a brush coating method, and then removing the solvent by heating at 40-60°C to form a dense and uniform protective layer; in this protective layer, FSI - Anions can accumulate at the interface, inducing the formation of an inorganic-rich SEI layer; the polyethylene backbone and imidazole cationic side chains provide mechanical flexibility and interfacial compatibility, enabling the protective layer to maintain structural stability during long-term cycling.
[0044] A modified lithium metal anode, comprising: Lithium metal substrate; and A protective layer covering at least one side surface of the lithium metal substrate, wherein the protective layer is the aforementioned artificial protective layer.
[0045] In this embodiment, the modified lithium metal anode is denoted as PVIMFSI@Li. Its preparation method is as follows: using a fresh lithium metal sheet with a thickness of 0.05–0.4 mm as a substrate, a PVIMFSI / DMSO solution is uniformly brushed onto the surface of the lithium metal sheet using a soft brush. After removing the solvent by constant heating at 40–60°C for 2–6 hours, a dense and uniform PVIMFSI artificial protective layer is formed on the lithium metal surface, resulting in the modified lithium metal anode. This modified anode has the following advantages: the protective layer provides uniform lithium-ion flux and nucleation sites, effectively inhibiting lithium dendrite growth; the inorganic-rich SEI layer induced by the protective layer has high mechanical strength and excellent lithium-ion transport performance, significantly reducing interface impedance; the good mechanical flexibility of the protective layer can buffer the volume change of lithium metal during charging and discharging, preventing the protective layer from cracking.
[0046] A lithium metal battery includes a positive electrode, an electrolyte, a separator, and a modified lithium metal negative electrode as described above.
[0047] In this embodiment, the lithium metal battery is specifically a coin-type LCO / PVIMFSI@Li battery; this battery uses PVIMFSI@Li as the negative electrode and lithium cobalt oxide (LCO) as the electrode, with an areal loading of 0.5–2.0 mAh / cm³. 2 The electrode was a positive electrode, and a porous polypropylene (PP) membrane was used as the separator. The assembly was performed in a glove box under an argon atmosphere. After assembly, the electrode and separator were allowed to stand to allow the electrolyte to fully wet them. Then, constant current charge-discharge tests, rate performance tests, and electrochemical impedance spectroscopy were conducted. The performance test results are as follows: Figure 1 and Figure 2 As shown; Figure 1 This indicates that the PVIMFSI@Li symmetric cell exhibits long-cycle stability exceeding 2000 h at high current density, with low and stable overpotential. Figure 2 This indicates that the LCO / PVIMFSI@Li battery retains 90 mAh g after 3000 cycles at a high rate of 5C. -1 It has a high discharge specific capacity and a capacity retention rate of up to 88%.
[0048] A method for preparing an ionic liquid polymer, comprising: In the presence of a free radical initiator, 1-vinyl-3-alkylimidazolium halide monomers undergo polymerization in an organic solvent to yield poly(1-alkyl-3-vinylimidazolium) halide; A poly(1-alkyl-3-vinylimidazolium) halide salt and a bis(fluorosulfonyl)imide salt are subjected to an ion exchange reaction in an aqueous solution to generate an ionic liquid polymer precipitate containing poly(1-alkyl-3-vinylimidazolium bis(fluorosulfonyl)imide); the precipitate is separated and purified from the reaction mixture to obtain the ionic liquid polymer.
[0049] The preparation method specifically includes the following two stages: The first stage is the polymerization reaction: 5-25g of 1-vinyl-3-butylimidazolium bromide (VIMBr) monomer and 20-40mL of N,N-dimethylformamide (DMF) are added to a 50mL three-necked flask. Nitrogen gas is continuously purged for 10-30min to completely remove oxygen from the system and create an inert reaction atmosphere. The flask is placed in an oil bath at 60-80℃ and magnetically stirred at 300-600r / min for 4-6h to completely dissolve and uniformly disperse the monomer. The initiator solution (50-150mg of azobisisobutyronitrile (AIBN) dissolved in 3-6mL of DMF) is quickly injected, and the reaction is continued at 60-80℃ with constant stirring for 12-36h to complete the free radical polymerization reaction. After the reaction was completed, the product was cooled to room temperature to obtain a brown sol product. The product was washed 2-4 times with deionized water and ethyl acetate (EA) alternately, and after each shaking, it was allowed to stand and separate into layers to obtain a yellow organic phase. The organic phase was transferred to a vacuum drying oven at 60-80℃ and dried for 12-24 hours to obtain a yellow solid powder PVIMBr.
[0050] The second stage is the ion exchange reaction: Weigh 1-3g of PVIMBr and dissolve it in 20-30mL of deionized water, and separately weigh 1-3g of LiFSI and dissolve it in 20-30mL of deionized water; Under stirring at 300-600r / min at room temperature, slowly add the LiFSI aqueous solution to the PVIMBr aqueous solution over 5-10min. After the addition is complete, continue stirring for 5-30min. The ion exchange reaction produces a white PVIMFSI precipitate; Centrifuge at 5000-10000r / min for 5-10min to collect the precipitate, and wash it repeatedly with deionized water 2-5 times until the washing solution is clear when silver nitrate solution is added; Dry the precipitate under vacuum at 60-80℃ for 12-24h to obtain a white powdery product, PVIMFSI.
[0051] Example 1: Cyclic Performance Test of Symmetrical Batteries PVIMFSI@Li was prepared as an electrode by brushing a PVIMFSI / DMSO solution onto the surface of a lithium metal sheet in an argon-atmospheric glove box. After removing the solvent by heating, a symmetrical PVIMFSI@Li / PVIMFSI@Li battery was assembled using a polypropylene (PP) membrane and injected with conventional lithium-ion battery electrolyte. Simultaneously, a comparative Li / Li symmetrical battery was assembled using a pure lithium metal sheet as an electrode.
[0052] Long-cycle testing was conducted under constant current charge-discharge conditions, and the results are shown in the attached figure. Figure 1 As shown. At high current densities (e.g., 10 mA / cm²), -2Under these conditions, the PVIMFSI@Li / PVIMFSI@Li battery still exhibits long-term cycling stability exceeding 2000 hours and displays stable and low overpotential, indicating a low energy barrier for the lithium deposition / stripping process. This is attributed to the FSI of the PVIMFSI artificial protective layer side chains. - Anions accumulate at the interface, inducing the formation of a stable SEI layer rich in inorganic phases such as LiF, LiN, and Li2O. This SEI layer exhibits excellent lithium-ion transport performance and significantly reduces interfacial impedance.
[0053] Example 2: Full Battery Cycle Performance Test The prepared PVIMMFSI@Li was used as the anode, with lithium cobalt oxide (LCO) as the electrode material, and the areal loading was 0.5–2.0 mAh / cm³. 2 Using polypropylene (PP) as the positive electrode and a polypropylene (PP) membrane as the separator, button-type LCO / PVIMFSI@Li batteries were assembled in a glove box under an argon atmosphere; at the same time, a control sample LCO / Li battery was assembled using pure lithium metal sheets as the negative electrode.
[0054] After the assembled battery was left to stand, it underwent constant current charge-discharge, rate performance, and electrochemical impedance spectroscopy tests. The results are shown in the attached figure. Figure 2 As shown; after 3000 cycles at a high rate of 5C, the LCO / PVIMFSI@Li battery still retains 90mAh g. -1 It exhibits a high discharge specific capacity and a capacity retention rate of up to 88%, demonstrating superior ultra-long cycle stability.
[0055] This superior performance is attributed to the synergistic effect of the multiple functions of the PVIMMFSI artificial protective layer: FSI - The anion-induced inorganic-rich SEI layer exhibits high mechanical strength and excellent lithium-ion transport performance, effectively suppressing the growth of lithium dendrite nuclei. The polyethylene backbone and imidazole cationic side chains provide good mechanical flexibility and interfacial compatibility, buffering volume changes during lithium deposition / stripping and maintaining the integrity of the film structure. The dense and uniform protective layer provides uniform lithium-ion flux and nucleation sites, fundamentally suppressing dendrite growth and ensuring the long-term cycle stability of the battery.
[0056] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above, and that the invention can be implemented in other specific forms without departing from its spirit or essential characteristics. Therefore, the embodiments should be considered in all respects as exemplary and non-limiting, and the scope of the invention is defined by the appended claims rather than the foregoing description. Thus, all variations falling within the meaning and scope of equivalents of the claims are intended to be included within the present invention. No reference numerals in the claims should be construed as limiting the scope of the claims.
[0057] Furthermore, it should be understood that although this specification describes embodiments, not every embodiment contains only one independent technical solution. This narrative style is merely for clarity. Those skilled in the art should consider the specification as a whole, and the technical solutions in each embodiment can also be appropriately combined to form other embodiments that can be understood by those skilled in the art.
Claims
1. A method for preparing an artificial protective layer for lithium metal anodes, characterized in that, Includes the following steps: Step S1: Dissolve the ionic liquid polymer containing imidazole cations in an organic solvent to obtain a coating solution; Step S2: Apply the coating liquid to the surface of the lithium metal substrate and remove the organic solvent to form the artificial protective layer on the surface of the lithium metal substrate.
2. The preparation method according to claim 1, characterized in that, The ionic liquid polymer is a hydrophobic ionic liquid polymer prepared by an ion exchange reaction; the ion exchange reaction occurs between the imidazolium halide polymer and the bis(fluorosulfonyl)imide salt.
3. The preparation method according to claim 2, characterized in that, Prior to step S1, the preparation method further includes the step of preparing the ionic liquid polymer: providing an aqueous solution of an imidazolium halide polymer; introducing a bis(fluorosulfonyl)imide salt into the aqueous solution to generate a precipitate containing the hydrophobic ionic liquid polymer; separating and washing the precipitate until no halogen ions are detectable in the washing solution.
4. The preparation method according to claim 2 or 3, characterized in that, The ionic liquid polymer is poly(1-butyl-3-vinylimidazolium bis(fluorosulfonyl)imide); the organic solvent is dimethyl sulfoxide; and the application method is brushing.
5. The preparation method according to claim 2, characterized in that, The mass concentration of the coating solution is 0.1–10.0 g / mL, and the organic solvent is removed by heat treatment at 40–80 °C in step S2.
6. An artificial protective layer for a lithium metal anode, characterized in that, The invention comprises a poly(1-alkyl-3-vinylimidazolium) ionic liquid polymer, the ionic liquid polymer comprising a polyethylene backbone and an imidazole cationic side chain, wherein the imidazole cation forms an ionic bond with a fluorinated sulfonamide anion.
7. The artificial protective layer according to claim 6, characterized in that, The fluorinated sulfonyl imide anion is a bis(fluorosulfonyl)imide anion, and the alkyl group is butyl; the artificial protective layer is prepared by the method according to any one of claims 1 to 5.
8. A modified lithium metal anode, characterized in that, include: Lithium metal substrate; as well as A protective layer covering at least one surface of the lithium metal substrate, wherein the protective layer is the artificial protective layer as described in claim 6 or 7.
9. A lithium metal battery, characterized in that, It comprises a positive electrode, an electrolyte, a separator, and a modified lithium metal negative electrode as described in claim 8.
10. A method for preparing an ionic liquid polymer, characterized in that, include: In the presence of a free radical initiator, 1-vinyl-3-alkylimidazolium halide monomers are polymerized in an organic solvent to obtain poly(1-alkyl-3-vinylimidazolium) halide; The poly(1-alkyl-3-vinylimidazolium) halide salt and the bis(fluorosulfonyl)imide salt are subjected to an ion exchange reaction in an aqueous solution to generate an ionic liquid polymer precipitate containing poly(1-alkyl-3-vinylimidazolium bis(fluorosulfonyl)imide). The precipitate was separated and purified from the reaction mixture to obtain the ionic liquid polymer.